Pharmacological properties and phytochemical components of Elaeocarpus: A comparative study - Susana Elya Sudradjat; Kris Herawan Timotius (Elsevier, 2022)
Background: Many species of Elaeocarpus, particularly Elaeocarpus ganitrus and Elaeocarpus sylvestris provide specific bioactive compounds that determine their pharmacological properties. Purpose: This review aimed to decipher and evaluate the updated information on core bioactive compounds and pharmacological benefits among Elaeocarpus species, particularly Elaeocarpus ganitrus and Elaeocarpus sylvestris. Methods: Relevant articles were searched from PubMed, Science Direct, and Google Scholar with the term ''Elaeocarpus.'' Results: Two most frequently researched species of Elaeocarpus are Elaeocarpus ganitrus (syn. E.sphaericus) and E. sylvestris. Their core bioactive compounds are alkaloids, phenolic and flavonoid compounds, and cucurbitacins. Elaeocarpus alkaloids have an affinity with the delta-opioid receptors (DOR). Many extracts of Elaeocarpus are rich in phenolic and flavonoid compounds that are potent antioxidants and inhibitors of several health-related enzymes, antivirus, antidiarrheic, and anticancer activities. Cucurbitacins from Eleaocarpus have potent anticancer properties.The main pharmacological properties of Elaeocarpus are CNS-related diseases, including antidepressant and analgesic activities, antimicrobial, anticancer, antivirus activities, and antihypertension. Conclusion: The core bioactive compounds of Elaeocarpus are alkaloids, phenolics and flavonoids, and cucurbitacins. They determine the pharmacological benefits of Elaeocarpus, particularly in treating CNS-related diseases (delta-opioid receptor-related disorders), infectious diseases (bacterial and virus), and cancer.